Removal Efficiency of Ammoniacal Nitrogen from Palm Oil Mill Effluent (POME) by Varying Soil Properties - Emra Elinda, Jefferson; Kanakaraju, Devagi; Meng, Guan Tay (Asian Network for Scientific Information, 2016)
Palm Oil Mill Effluent (POME) contains large amounts of organic matters and nutrients. Instead of discharging into oxidation ponds, POME can be used as an alternative option to replace inorganic fertilizers which have been known to increase the hardness and acidity of the soil over time. This study investigated the effect of different soil properties on the ammoniacal nitrogen removal efficiencies in POME. The ammoniacal nitrogen removal efficiencies from three mediums over 7 days of retention times were studied. Medium I contained major amount of sand, whereas medium II contained major amounts of clay and lastly medium III contained large amounts of silt and clay. The results showed that medium II produced the highest removal efficiency of ammoniacal nitrogen in POME, with the average removal efficiency of 77±5.1%. The average values of removal efficiencies obtained from mediums I and III were 61±6.2 and 58±11.3%, respectively. In addition, the removal efficiency of ammoniacal nitrogen increased slowly with the retention time. Medium II recorded the highest removal rate (k = 0.0897 dayG1) compared to mediums I (k = 0.0435 dayG1) and III (k = 0.0492 dayG1). The mechanism of removal ammoniacal nitrogen from the medium occurred via absorption by the soil particle.